Marginalisasi Bahasa Indonesia di Ruang Publik Digital terhadap Dominasi Bahasa Asing dan Dampaknya pada Identitas Nasional - Sifa Khoirun Nisa; Siti Enik Mukhoiyaroh Bambang; Auli Lestari Manik (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to analyze the phenomenon of the marginalization of the Indonesian language in the digital public sphere and its implications for the sustainability of national identity. Amid the tide of globalization and technological advancements, the use of foreign languages and mixed languages is increasingly dominating communication on social media, potentially displacing the Indonesian language’s role as a symbol of national identity. This study employs a netnographic method, which allows for the observation of natural and contextual language interactions on digital platforms such as TikTok and Instagram. This approach was chosen because it captures authentic language practices as well as the social meanings behind language use within online communities. The results indicate that the marginalization of Indonesian in the digital public sphere is marked by high levels of foreign language use, code-mixing, and a shift in language preferences among the younger generation influenced by factors such as prestige, globalization, and popular culture. This phenomenon not only impacts linguistic aspects but also implies a weakening of national identity as a nation founded on a unifying language. Nevertheless, the digital public sphere also has the potential to serve as a means of strengthening identity if Indonesian is used consistently and adaptively. Therefore, strategic efforts are needed through language policy, education, and digital literacy to ensure the continued vitality of the Indonesian language. This study is expected to make theoretical and practical contributions to the development of sociolinguistic research and the strengthening of national identity in the digital age.